A Phylogenetic Study Of Marek’s Disease Virus Glycoprotein L In Iraqi Layers’ Farms - Mohammed Salih Abdulrasool, Layth; Bara Allawe, Aida (Journal of Neonatal Surgery, 2025)
Marek’s virus disease (MDV) is an important avian disease of tumorigenesis nature, immunosuppression outcome, and significant economic impacts. The disease is controlled by mass vaccination supported with good management practices that restrict tumor formation. However, these practices failed in controlling virus spread which continues to evolve and cause field infections, implying a possible negative role for vaccine in driving virus mutations and virulence. In this study, 160 clinical samples were collected from 50 layers’ flock from ten different Iraqi provinces, were examined by real-time PCR against the polyprotein (pp38) gene of MDV using specific primers. The results revealed that 28 samples originated from 12 farms of four provinces were positive. Next, eight positive samples were selected according to their high yield viral genome which was represented by high Cycle threshold (Ct) ratio, amplified by glycoprotein L (gL) specific primers through conventional PCR. The PCR products were sent to commercial sequence company (Macrogen/ South Korea) and Upon results feedback, sequence alignment and phylogenetic relatedness study of viral glycoprotein L was carried out. The results found multiple Single Nucleotide Polymorphisms (SNP) among the local strains compared with reference one, where six out of eight samples carry a gL genome that matched 98-100% of circulating viruses previously described from the region. Also, the results found that two sequences showed a highly variable sequence with 93% and 85% identity match with other described viruses sequence of gL. This study represents the first attempt to investigate the gL of MDV in Iraqi poultry farms.